An Analysis of Theme Development of The Movie "Armageddon" - Ni Putu, Ayu Wendiari Septika; Winarta, Ida Bagus Gde Nova; Juniartha, I Wayan (Journal of Language and Applied Linguistics, 2024)
This research focuses on the transcription and the script of the movie Armageddon by Robert Roy Pool and Jonathan Hensleigh. In this study the writer used qualitative method in collecting the data. This research used theory from (Schuster, 1966). The findings show there are three themes such as Love Theme, Patriotism Theme and Survival Theme. Love theme explained about the love story between Grace and A.J. between Harry Stamper as Grace's father who is also her second boss. Meanwhile, in patriotism theme, it is explained by the existence of a special mission from NASA for professional drillers to go out into space in order to save the earth and The survival theme is shown by various strategies and struggles carried out by NASA through the formation of a drilling team to save the world through Harry's team.